Unionization and deprofessionalization: Which comes first? - Joseph A. Raelin (Journal of Organizational Behavior, 1989)
This paper constitutes a review of the question whether unionization leads to deprofessionalization or whether deprofessionalization occurs first to be followed by union efforts to restore professional status to a profession under attack from social, political, and economic forces, including the bureaucracy. The evidence mustered from the historical literature appears to support the latter hypothesis, although it is questionable whether a union by itself can return an established profession to its original status prior to deprofessionalization.
Keywords: J50; J51; M12; M54; 330; labor relations; unions; professionals; deprofessionalization; unionization; professional associations; nursing